Statistical self-similarity in time series from financial data & chaotic dynamical systems - Zhang, Panpan (Wake Forest University, 2012)
In this paper, I am going to introduce statistical self-similarity for discrete time series. My thesis is divided into three parts:
Keywords: discrete wavelet transform; fractional Brownian motion; Multiresolution analysis; self-similarity; stationary increments; wavelet coefficients